Evalution of Anti-Arthritic Potential of Siddha Formulation ChanthirothayaMathirai on Freund‘s Adjuvant-Induced arthritis in Wistar rats (Asian Journal of Pharmaceutics (AJP), 2022)
Introduction: Rheumatoid arthritis (RA) is an autoimmune, chronic multisystem disease with various systemicmanifestations resulting in joint damage and physical disability. The Siddha system of medicine is one of thetraditional system of Indian medicine, which comprises ennumber of siddha formulations for RA. The tabletChanthirothayaMathirai (CHTM), a herbomineral siddha formulation is found to be efficacious for RA. Thepresent study focuses on theevaluation of anti-arthritic potential of Siddha formulation CHTM on completeFreund’s adjuvant (CFA)-induced arthritis model. Materials and Methods: The animals were grouped into three.Group I received normal saline, Group II received 0.1 ml of CFA in the left hind and treated with 250 mg/kg ofCHTM from day 1 to 21, and Group III received 0.1 ml of CFA into the left hind and treated with 500 mg/kg ofCHTM from day 1 to 21. The biochemical parameters were carried out on all groups after 21 days. The presenceof any adverse effects was also recorded throughout the study. Results: A significant increase in the paw volumeand thickness of CFA-injected paws compared to the normal control paws was observed. Arthritic assessmentscoring revealed that CFA-injected paws were with the maximum scoring of 3.8. The treatment with CHTM atboth doses has significantly decreased arthritic scoring to 2.3. Results showed marginal signs of rejuvenation withmild cartilages destruction with restoring histology of synovium and bone morphology were observed in low-dosedrug-treated rats. High-dose drug-treated rats showed normal histomorphology of synovium. Conclusion: Thestudy concluded that the trial drug CHTM at the dose of 250 and 500 mg/kg showed a significant reduction in jointswelling with a reversal in bone and tissue morphology. Thus, CHTM formulation offers a strong protective effectagainst Freund’s complete adjuvant-induced paw edema in rats. Hence, the drug CHTM has been scientificallyvalidated for its anti-arthritic potential in management of RA.